Perbandingan Mutu Biji Kopi Robusta (coffea canephora) Hasil Pengeringan Secara Pengasapan dan Penjemuran Di Perkebunan Kopi Desa Purworejo Kabupaten Bolaang Mongondow Timur - Moh Fadel Alhabsyi; Lady C. Ch. E. Lengkey; Maya M. Ludong (COCOS, 2021)
AbstractThe purpose of this research are 1)Determine changes in moisture content and durationof drying the coffe beans resulting from drying by smoking and drying in the sun. 2)Comparingthe drying rate of coffee beans dried by smoking and drying in the sun, 3)Determine the qualityof coffee beans produced from the drying process by smoking and drying in the sun. The result ofthis study showed coffee beans that are dried by smoking and drying can produce good qualitycoffee beans. Coffee beans dried by smoking 11.04% moisture content, 9 hours of drying time,5.79% drying rate, 82.75 coffee quality. Coffee beans dried by drying 12.68% moisture content,23 hours or 6 days of drying time, 2.20% drying rate, 80.75 coffee quality.Key words: determine quality, drying robusta coffee beans, smoking and sun drying,coffee beans.Email respondensi: Fadelalhabsyi97@gmail.com